2002
DOI: 10.1038/sj.cr.7290115
|View full text |Cite
|
Sign up to set email alerts
|

Targeting epidermal Langerhans cells by epidermal powder immunization

Abstract: Immune reactions to foreign or self-antigens lead to protective immunity and, sometimes, immune disorders such as allergies and autoimmune diseases. Antigen presenting cells (APC) including epidermal Langerhans cells (LCs) play an important role in the course and outcome of the immune reactions. Epidermal powder immunization (EPI) is a technology that offers a tool to manipulate the LCs and the potential to harness the immune reactions towards prevention and treatment of infectious diseases and immune disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…It has been known that the epidermal layer harbors a variety of immunocompetent cells including epidermal Langerhans cells, which are major histocompatibity complex (MHC) class II-positive antigen-presenting cells; keratinocytes; and CD4 + and CD8 + T cells [22]. One hypothesis for the skin vaccination is that immunocompetent cells, most likely Langerhans cells, capture the antigens, which are subsequently delivered into local lymph nodes and prime immune responses [23]. By visualizing the expression of the β-galactosidase gene, we found that adenoviral vectors are able to deliver the genes across the skin and primarily appear in the epidermal layer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that the epidermal layer harbors a variety of immunocompetent cells including epidermal Langerhans cells, which are major histocompatibity complex (MHC) class II-positive antigen-presenting cells; keratinocytes; and CD4 + and CD8 + T cells [22]. One hypothesis for the skin vaccination is that immunocompetent cells, most likely Langerhans cells, capture the antigens, which are subsequently delivered into local lymph nodes and prime immune responses [23]. By visualizing the expression of the β-galactosidase gene, we found that adenoviral vectors are able to deliver the genes across the skin and primarily appear in the epidermal layer.…”
Section: Discussionmentioning
confidence: 99%
“…By mechanically penetrating the cell membrane, the particles are delivered straight into the cytoplasm and/or the nucleus of the cells, thereby circumventing the suboptimal uptake of DNA from extracellular spaces. This allows for high immunogenicity at very low doses and superior induction of CTLs, but also antibodies (reviewed in [32]). These properties render gene gun immunization extremely interesting for immunization against pre-erythrocytic stages of malaria.…”
Section: Advanced Methods For Vaccine Applicationthe Biojector™ and Tmentioning
confidence: 98%
“…Antigen rapidly diffuses from the vaccination site, and is efficiently endocytosed by LCs. Initially, nearly all LCs in the vicinity of the target site can be shown to contain antigen [61]. Levels of antigen and antigen-containing LCs are high for 2 days following vaccination, and remain present at the site for ≤ 5 days.…”
Section: Delivery Of Protein Vaccines By Epidermal Powder Immunisationmentioning
confidence: 99%